Reviews and notices - Ann-Marie Svensson; Marko Modiano; Angela Karstadt; Mats Mobärg; Åke Persson; Monica Armini; Peter Boxall; Maria Proitsaki; Ronald Paul; Sabina Kielow; Lars-Olof Nyhlén; Sigurd Rothstein; et al. (Moderna Språk)
Includes the following reviews: